Synthesis strategies of iron nitrides at carbon cloth as battery-like electrode for hybrid supercapacitors - Kordek-Khalil, Karolina; Moyseowicz, Adam; Moyseowicz, Agata K. (Frontiers in Materials, 2023)
In recent years, hybrid supercapacitors (HSCs) or supercapatteries which combine a capacitor-type electrode with an electrode based on materials exhibiting a Faradaic (battery-like) response have been intensively investigated for next-generation energy storage applications. HSCs attracted great attention due to a significant increase of maximum energy density stored while providing stable long-term performance and good rate capability. However, the electrochemical performance of the device is closely related to the inherent properties of the electrode material, including morphology and structure. In this paper, we present synthesis protocols for iron oxide/hydrophilic carbon cloth (Fe2O3@hCC) composite electrodes and their electrochemical performance as a negative electrode operating in an alkaline electrolyte. Two environmentally friendly, scalable and facile synthesis approaches were applied, including hydrothermal treatment and direct electrodeposition. Next, the Fe2O3@hCC electrodes were treated to convert iron oxide to iron nitride (Fe2N). The results showed that the synthesis of the precursor for iron nitride has a direct impact on morphology, crystalline structure and electrochemical performance. Furthermore, the amorphous Fe2N obtained from electrodeposition exhibited significantly better Faradaic behavior, achieving a specific capacity up to 186 mAh g -1 , 66% higher than the composite electrode with Fe2N from the hydrothermal approach.This is a provisional file, not the final typeset article As a result, a great deal of focus has been placed on the development of supercapacitor electrode materials to improve energy storage performance and meet the high demand for modern electronic devices. Electrode materials based on transition metal compounds, such as metal oxides, metal hydroxides, metal sulfides, and metal nitrides, are regarded as optimal for highly efficient electrochemical capacitors and hybrid supercapacitors (HSCs) (